REVIEW OF MODERN PHYSICAL AND GEOGRAPHICAL FEATURES OF WESTERN KAZAKHSTAN IN THE CONTEXT OF GLOBAL CLIMATE CHANGE (Journal of Geography and Environmental Management, 2025)
This paper examines the current physical and geographical conditions of Western Kazakhstan in the context of changing climate parameters. Climate, as one of the most critical factors influencing the dynamics and development of modern natural systems, significantly affects all landscape-forming components. The global, dynamic changes in the thermal regime of the near-surface atmospheric layer are expected to lead to the degradation of natural landscapes. The study highlights that over a relatively short period, shifts in climatic factors do not result in equally rapid changes in the lithogenic foundation of natural systems. This assumption is supported by both field research results and a review of relevant literature. The research involved a comparative analysis of literature sources, modern cartographic data, and satellite imagery. Additionally, statistical analysis was conducted on trends in the annual average near-surface air temperature and the annual amount of atmospheric precipitation based on field observation points. The results of field and laboratory studies indicate the stability of the lithogenic base of natural systems, including geological and geomorphological structures and soil-forming processes. In contrast, vegetation and surface waters show cyclical changes, reflecting natural shifts between wetter and drier periods. The study concludes that, in the absence of direct anthropogenic pressure, natural systems are unlikely to undergo fundamental transformation within just a few decades. For such substantial changes to occur under the current climate change trends, a significantly longer period would be required.
Keywords: landscape; natural system; natural zone; lithogenic foundation; climate indicators; degradation